HARMONISASI SISTEM GILIR AIR IRIGASI BERBASIS WILAYAH SUNGAI UNTUK DAERAH IRIGASI RAWAN KONFLIK - Sugiharta, Sugiharta; Juanita, Juanita; Endi Alfian, Muhammad (Yayasan Nusantara Hasana Berdikari, 2025)
The Babak Watershed has 44 dams that operate to meet irrigation water needs in the regencies of Central Lombok and West Lombok. One of the dams in the Babak watershed is the Jurang Sate Dam, which has a service area larger than any other dam in West Nusa Tenggara. Under the condition of irregular water availability, Jurang Sate Dam is required to meet the irrigation water needs of Jurang Sate Hulu, Jurang Sate Hilir, Jurang Batu Hulu and Jurang Batu Hilir, covering an area of 8,671 ha with 3 (three) planting seasons. The research method will focus on primary data processing in the form of field cropping patterns, real time water availability and secondary data in the form of analysis of potential water availability, K factor and FK class and water balance through water sharing system in the field. The results of this research will provide a water shifting method that is the result of an agreement both technically and institutionally